Perfil clínico dos pacientes com LLC-B do Ambulatório do Hospital Universitário Walter Cantídio/Hemoce : corelação com marcadores biológicos de prognóstico - Machado, Rosângela Pinheiro Gonçalves (2009)
Introduction: Chronic lymphocytic leukemia (CLL) is a neoplasm characterized by clonal proliferation of lymphocytes of mature appearance. Clinically and prognostic heterogeneous. Rai and Binet established clinical prognostic systems that classify LLC in low, intermediate and high risk. Soon, the biological markers of prognosis that increased the predictive power of the LLC. Objective: To characterize the clinical and biological markers of pognóstico of patients with CLL the outpatient department of a university hospital (HUWC) / Center for Hematology and Hemotherapy Ceará / HEMOCE). Methodology: This is a retrospective, cross-sectional and observational 43 patients LLC, recruited so randomisation, from August 2007 to June 2009. We collected patient data from medical records, interview and three samples with 5.0 ml of peripheral venous blood in ethylenediaminetetraacetic acid (EDTA) for blood, for automated methodology CellDyn ® equipment, model 3500, measurement of ß2-microglobulin (ß2 - M) serum by automated quantitative test on the device MINI-VIDAS (BioMérieux ®) and immunophenotyping on flow cytometry Beckman Coulter ® EPICS XL-MCL (Coulter). Then collect the puncture of bone marrow aspirate and bone marrow examination for 4 to 5 ml in 2 ml of heparin for cytogenetic evaluation by Banda - G. Data analysis was performed using the statistical programs Biostat 4.0 and GraphPad Prism (version 5.00), the Phi coefficient test and the test coefficient Contingency C. The Fisher and chi-square test with significance level α = 5%. Kaplan-Meier survival function and log rank test. The results were generated using the free software R, version 2.7. Results: The patients (74.42%) were aged over 60 years, 58.14% 41.86% men and women, the majority (32.56%) worked in agriculture; brown (74.42%), coming the capital (53.49%), family history of unknown LLC (46.51%), symptomatic at diagnosis (53.49%), with comorbidity (arterial hypertension and Diabetes Mellitus) (51.16%), stage 0 ( 34.89%), I and II (51.16%), III and IV (13.95%) Rai, A (44.19%), B (44.19%) and C (11.62%) of Binet, lymphocyte doubling time (SRT) absent (81.40%), bone marrow biopsy with non-diffuse pattern (57.14%), lactate dehydrogenase (LDH) normal (83.72%), valued at diagnosis. The tests obtained during the course of the patients showed an immunophenotypic profile of classic B-CLL with expression of CD5 +, CD19 +, CD23 + surface immunoglobulin and low-expression, most with Zap-70 negative (77.50%); expression CD38 negative (73.81%), beta-2 microglobulin increased (55.81%), normal karyotype (44.4%) and genetic alterations in 11, 11% by classical cytogenetics. Survival curves of patients with Zap-70 negative and CD38 showed longer survival free of treatment. Conclusion: The patients studied were elderly, to encourage improve with late diagnosis due to the socioeconomic context, LLC indolent presented by classical staging criteria (Rai, Binet, TDL, standard bone marrow histology, LDH) and biological (the expression of Zap -70 and CD38), except for beta-2 microglobulin, but without statistical significance. Those with Zap-70 and CD38 negative had higher survival free of treatment. Male patients showed progress and prognosis similar to female. The prevalent treatment was associated with chlorambucil prednisone and did not lead patients to clinical remission or hematologic. The prognostic markers of the correlation tended to identify patients within the subgroups of risk.